Direct oral anticoagulant (DOAC) monitoring within primary care: a quality improvement project - Isobel Joy McFadzean; Rhian Francis; Catrin Fischetti; Vanessa Morton; Susan Goodfellow (BMJ Open Quality, 2023)
Background Poor monitoring of anticoagulants is a significant area of patient safety. It can lead to the dichotomous risk of haemorrhage/clotting without appropriate counselling and monitoring. While healthcare professionals may be familiar with the anticoagulant warfarin and the international normalised ratio, they might be unaware of the monitoring requirements of direct oral anticoagulants (DOACs), despite DOACs making up 62% of anticoagulants prescribed. The goal of this quality improvement (QI) project was to increase the compliance of monitoring of DOACs within general practice (GP) to improve patient safety and reduce the risk of an adverse outcome for patients.Local problem In 2019, the GP surgery had 318 patients prescribed a DOAC and their medication reviews took place opportunistically. While initially, monitoring levels were nearly 100%, by December 2018 this had dropped significantly, and clinicians stated they were unfamiliar with this medication.Methods and interventions This project aimed to resolve this by using QI methodology and Plan–Do–Study–Act (PSDA) cycles to create new sustainable processes with DOAC monitoring and aimed to increase DOAC monitoring by 20% within 6 months.Results Within 6 months, the project improved the rate of monitoring, and 49% of all patients prescribed a DOAC were seen in a DOAC clinic (n=156) and 78% (n=230/294) had DOAC counselling; 97% (n=295/304) had appropriate blood tests and 72% (n=216/298) had a recent weight recorded within their medical records. Three years on, 600 patients within the practice are prescribed DOACs and 74% (n=445) have had an annual review adhering to the gold standards set within the project.Conclusion This QI project confirms that monitoring of DOACs can be improved within primary care by using QI methodology and improving patient safety, using PDSA cycles, stakeholder engagement and the introduction of the anticoagulant domains within the nationwide Quality Assurance and Improvement Framework.